Ethical challenges in health care developing your moral compass - Lachman, Vicki D. (Springer Publishing, 2009)
Presents the issues and dilemmas facing nurse practitioners and health care managers in identifying and sustaining ethical practice and management. This handbook outlines both personal and organizational strategies to develop moral courage when facing such dilemmas. It combines discussions of ethical contexts with practical case studies.